Interactive identification key to all brittle star families (Echinodermata; Ophiuroidea) leads to revised morphological descriptions - Goharimanesh, Mona; Stöhr, Sabine; Mirshamsi, Omid; Ghassemzadeh, Fereshteh; Adriaens, Dominique (European Journal of Taxonomy, 2021)
Ophiuroidea is the largest class among extant echinoderms, with over 2000 described species assigned to 33 families. Here, the first identification key to the recently revised classification was developed, and revised morphological descriptions were derived from it, expanding the previous short diagnoses. The key was built by analyzing internal and external skeletal characters of predominantly the type species of each family, including at least two mutually exclusive attributes per family. Various numeric and multistate characters were used to create a traditional as well as an interactive key using the DELTA and Xper software programs. Illustrations (SEM and digital photos) are included in the key to facilitate the assessment of character states by users. Not only is it the first identification key to the families, according to the recently proposed new classification and the examined species, but this interactive key also assists users in understanding the family level taxonomy of brittle stars. The interactive key allows new characters and states to be added, when more species will have been analyzed, without the need to reconfigure the complete key (as may be necessary with conventional keys).